Innovation of Government Research and Development Institution Based on Knowledge Management and Information Technology (Case Study on the Government Policy-Making Research and Development Institution) - Umi Rusilowati; Hadi Supratikta; Raden Roro Ayu Metarini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study investigates and analyzes knowledge-management-based innovation in developing knowledge sharing and absorbing and the role of Information-Technology-based innovation in supporting knowledge management. It is now a demand that institutions prioritize on creating innovation. Organizations that are able to compete can learn and be creative, which is only possible if the knowledge sharing within the institution is carried out properly. This is also the case for R&D institutions that must make innova-tions based on knowledge management and information technology. This is a single case study qualitative analysis. Based on criteria, four in-formants were selected as sources. They were interviewed guided by a list of open-ended questions. The results of this case study provide information on the aspects that are needed to support innovation in government R&D institutions. They also fill the gap in research on knowledge management. Inovation based on knowledge management processes in developing activ-ities to share and absorb knowledge in government R&D institutions has been running and has produced several innovations. IT has been utilized to share and absorb knowledge and it is a requirement for a functional official researcher, but there is still limited availability of computers.